An Empirical Bayesian Method for Detecting Differentially Expressed Genes Using EST Data. (20th January 2008) - You, Na; Liu, Junmei; Mao, Chang Xuan
Abstract : Detection of differentially expressed genes from expressed sequence tags (ESTs) data has received much attention. An empirical Bayesian method is introduced in which gene expression patterns are estimated and used to define detection statistics. Significantly differentially expressed genes can be declared given detection statistics. Simulation is done to evaluate the performance of proposed method. Two real applications are studied.